IMPLEMENTASI SISTEM ABSENSI BERBASIS GPS PADA PERANGKAT MOBILE UNTUK MONITORING KEHADIRAN SISWA DI SMK TARUNA ABDI BANGSA - Sari, Atika; Suwartika Kusumadiarti, Rini; Mecca Sufyana, Candra (INFOKOM (Informatika & Komputer), 2025)
Student attendance management is a crucial aspect of the educational process, closely related to student discipline, learning engagement, and performance evaluation. However, conventional manual attendance systems widely used in schools still suffer from several weaknesses, including vulnerability to data manipulation, delayed recapitulation, and a lack of transparency. With advancements in information and communication technology, leveraging GPS (Global Positioning System) technology on mobile devices presents a novel alternative for a more modern, efficient, and accurate attendance system. This research aims to design, develop, and implement a GPS-based attendance system on mobile devices that enables automatic recording of student attendance based on their geographical location. The methodology employed is Research and Development (R&D), utilizing a prototype model that encompasses stages of needs analysis, system design, development, testing, and evaluation. The implementation results indicate that the GPS-based attendance system can reduce proxy attendance practices, enhance administrative efficiency, and provide real-time attendance data that can be monitored by both school authorities and parents.